PEMBUDIDAYAAN TANAMAN PENGUSIR NYAMUK (REPELLENT) DAN PENGOLAHANNYA DI KAMPUNG SEREH KABUPATEN JAYAPURA - Brechkerts Lieske A Tukayo; Dzukharian Munandar; Qoriah Nur (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
There are many reports of negative effects of the use of DEET, N-Dietil-m-toluamida, so it is necessary to develop natural ingredients that are able to replace DEET as the active ingredient of repellent. Some plants around the house that can be used as repellent such as papaya, cloves, selasih, oranges, kecombrang, legundi, marigold, zodia, betel, and melt. Utilization of this plant is expected to reduce the rate of malaria transmission through prevention of malaria vector bite. This community service was carried out for 5 months in Sereh village Jayapura district in June-October 2021. Activities carried out ranging from surveying the existence of repellent plants in Sereh village, continued with community education about plants that have the potential to be repellent and cultivation of those plants and about malaria. After counselling, posters and pocket books were distributed. Then the community was given four types of repelelent plants (mint, kecombrang, lavender and black cumin) to representatives of 9 RW. Then the creation of garden at the Sereh village office in which repellents plant were planted. Evaluation conducted in the form of monitoring of repellent tannanan cultivated with the community, as well as achieving the initial target of benefits of repellent plants. The results of the evaluation showed that plants that do not require special conditions such as black cumin, kecombrang, and lavender can grow well, but many mint leaves do not succeed. Based on interviews with the community, existing plants can help to repel mosquitoes. This shows that cultivating repellent plants in people's homes can play an important role in malaria prevention.